DIGITAL TRANSFORMATION AND ITS IMPLICATIONS FOR MODERN ECONOMIC STRUCTURE: WARMINDO ONLINE SELLING AND BUYING STUDY - Marco Syahin Alam; Satria Putra Arsibal; Rayhan Wahyudistira (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This research aims to delve deeper into the phenomenon of digital transformation in the context of online warmindo (traditional Indonesian hot noodle soup) buying and selling, exploring its impact on the modern economic structure, and highlighting the challenges and opportunities that arise with these changes. The research method employed adopts a qualitative descriptive approach where data is collected from interviews and a review of previous research literature. Data analysis will involve the processes of reduction, presentation, and drawing conclusions to identify patterns, trends, and implications arising from this research. The results of the research indicate that this phenomenon has a significant impact on the modern economic structure, particularly in the culinary sector. Digital transformation opens up new opportunities for warmindo business operators to enhance product visibility, reach a wider market share, and improve operational efficiency through the adoption of technology.